CRISPR loss of function screening to identify genes involved in human primordial germ cell-like cell development. - Young Sun Hwang; Yasunari Seita; M Andrés Blanco; Kotaro Sasaki (PLoS Genetics, 2023)
Despite our increasing knowledge of molecular mechanisms guiding various aspects of human reproduction, those underlying human primordial germ cell (PGC) development remain largely unknown. Here, we conducted custom CRISPR screening in an in vitro system of human PGC-like cells (hPGCLCs) to identify genes required for acquisition and maintenance of PGC fate. Amongst our candidates, we identified TCL1A, an AKT coactivator. Functional assessment in our in vitro hPGCLCs system revealed that TCL1A played a critical role in later stages of hPGCLC development. Moreover, we found that TCL1A loss reduced AKT-mTOR signaling, downregulated expression of genes related to translational control, and subsequently led to a reduction in global protein synthesis and proliferation. Together, our study highlights the utility of CRISPR screening for human in vitro-derived germ cells and identifies novel translational regulators critical for hPGCLC development.